Developing Web-Based E-LKPD with PjBL Model to Student Competence in Scripting - Fadiyatul Muqtashidah; Ekohariadi (Journal of Education Technology and Information System, 2025)
The purpose of this research is to develop a website-based E-LKPD with a project-based learning model and then to improve students' psychomotor competence in Web Programming subjects, especially in client-side scripting materials using the E-LKPD. The design is carried out using the Research and Development (R&D) method and the ADDIE development model. The research was conducted at SMKN 1 Cerme with class XI TKJ 2 totaling 30 students as research subjects. Based on these conditions, this study will implement One Group Pretest-Posttest Design. The validation results obtained from the media validation test were 92% (very feasible), material validation was 93% (very feasible), teaching module validation or lesson plan was 87% (very feasible), and validation of pretest-posttest questions was 89% (very feasible). The validation results obtained an average of 90%, which can be concluded that the website-based E-LKPD application is very feasible to be applied in the learning process. The results of the hypothesis test analysis showed a significance of 0.001 where the result was less than 0.05. Based on these results, it can be concluded that H0 was rejected and H1 was accepted. Therefore, the application of website-based E-LKPD with a project-based learning model has a significant influence on students' psychomotor outcomes.